SISTEM INFORMASI PELAYANAN SIM - Matsaini Matsaini; Sholeh Rachmatullah (JURNAL TEKNIK INFORMATIKA, 2021)
The driving license administration service system is a special service provided by Nasional Police to people who want to make a SIM. This service system can be done online. The current application has made it a lot easier in the process of making up the SIM card production. However, there are some problems related to internal reports that must be reported because the service is not yet available in an existing application, so some recapitulation processes are still done conventionally and technical constraints on the server network. This study aims to create a service management information system application (SIMPEL SIM) that can provide solutions to internal reporting and server network technical constraints. The method used software development is waterflow. This application handles the printing of bank payment receipts automatically, granting the applicant's registration number automatically, printing the SIM application form on the form provided. Verification of the completeness of the file, validation of the score of the theory test, practice 1 and practice 2, validation of sim issuance and printing of temporary sim numbers if there is a technical problem in the existing network server. The use of the SIMPEL SIM application makes it easy to recapitulate internal reporting and can improve public services.